Sustainable supplier selection and order allocation through quantity discounts. Issue 1 (2nd January 2018) - Nourmohamadi Shalke, Parvin; Paydar, Mohammad Mahdi; Hajiaghaei-Keshteli, Mostafa
Abstract: Within activities related to the global supply chain, proper supplier selection regarding sustainability issues, especially economic, environmental and social, plays an important role in sustainable development. In this paper, a new multi-objective mathematical programming model is designed to consider sustainable supplier selection and order allocation simultaneously in a multi-period, multi-item and multi-supplier supply chain. In addition, quantity discounts are considered under two assumptions: all-unit and incremental. The proposed model is solved following a revised multi-choice goal programming approach in order to find a compromise solution. Furthermore, a real-life case is studied to justify the applicability of the proposed model.